1997
DOI: 10.1021/bi971125s
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans Mediate Cell Surface Oligomerization of Chemokines

Abstract: Chemokines are 8-10 kDa proteins involved in the control of leukocyte trafficking and activation. In free solution, chemokines are monomers at physiologic concentrations, although many multimerize at higher concentrations. Cell surface heparan sulfate may sequester chemokines, increasing their local concentrations and facilitating their binding to receptors expressed on leukocytes. In competitive binding assays using immobilized heparin, a 2-3-fold increase in the bound radiolabeled chemokine was seen with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
415
2
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(443 citation statements)
references
References 31 publications
(44 reference statements)
17
415
2
3
Order By: Relevance
“…7,8 It has been proposed that cell surface GAG form a scaffold within which chemokines are assembled into multimers. 45 While MCP-1 has been found as a dimer in solution at concentrations in the physiological range and as a tetramer at higher concentrations, this appears to have no functional significance as obligate monomers show a normal activity. 35,42,44 Chemokine multimerization within the cell surface GAG layer could provide a further explanation for the focal distribution observed for MCP-1.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinmentioning
confidence: 98%
See 1 more Smart Citation
“…7,8 It has been proposed that cell surface GAG form a scaffold within which chemokines are assembled into multimers. 45 While MCP-1 has been found as a dimer in solution at concentrations in the physiological range and as a tetramer at higher concentrations, this appears to have no functional significance as obligate monomers show a normal activity. 35,42,44 Chemokine multimerization within the cell surface GAG layer could provide a further explanation for the focal distribution observed for MCP-1.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinmentioning
confidence: 98%
“…45 In order to investigate this possibility, an obligate monomeric MCP-1 mutant P8A was added to the basal chamber and immunoreactive protein was subsequently identified on the apical surface of the model endothelium. As for the wild-type chemokine, it was found that the mutant protein was largely concentrated into focal regions on the apical surface of 26% (23 of 87 cells examined in 29 preparations) of the cells (Figure 3e).…”
Section: Distribution Of Mcp-1 On Eahy926 Cells By Immunofluorescencmentioning
confidence: 99%
“…First, chemokines indirectly mediate firm adhesion by activating leukocyte integrins to bind their endothelial ligands with high affinity [4,5]. In this instance, chemokines are presented to leukocytes through immobilization on glycosaminoglycans on the luminal surface of the endothelium [6,7]. Second, the chemotactic properties of chemokines direct leukocyte migration out of the vessel lumen and into the tissue [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The functional importance of chemokine-HS interactions has been shown in vivo, because administration of modified chemokines that exhibit reduced affinity to HS or heparin resulted in diminished leukocyte recruitment (31,32). Other functions of glycosaminoglycan-chemokine interactions have been proposed, including the formation of immobilized chemokine gradients in the extracellular matrix and the protection of these mediators from degradation, resulting in the prolongation of their activities (15,35,36).…”
mentioning
confidence: 99%